2023
DOI: 10.3390/nu15122714
|View full text |Cite
|
Sign up to set email alerts
|

IgE-Mediated Shellfish Allergy in Children

Abstract: Shellfish, including various species of mollusks (e.g., mussels, clams, and oysters) and crustaceans (e.g., shrimp, prawn, lobster, and crab), have been a keystone of healthy dietary recommendations due to their valuable protein content. In parallel with their consumption, allergic reactions related to shellfish may be increasing. Adverse reactions to shellfish are classified into different groups: (1) Immunological reactions, including IgE and non-IgE allergic reactions; (2) non-immunological reactions, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 137 publications
0
15
0
Order By: Relevance
“…The onset of peanut, tree nut, fish, and shellfish allergies tends to be later than milk, egg, soy, and wheat, with estimated peak prevalence at 1 ½ to 3 years of age [ 19 , 21 , 56 , 57 ], although the shift towards early introduction of these foods has led to a corresponding reduction in age at diagnosis of these allergies. In addition to presenting later, nut and seafood allergies also tend to persist into adulthood, which will be covered more in the following sections (Table 1 ).…”
Section: Infancy and Early Childhoodmentioning
confidence: 99%
“…The onset of peanut, tree nut, fish, and shellfish allergies tends to be later than milk, egg, soy, and wheat, with estimated peak prevalence at 1 ½ to 3 years of age [ 19 , 21 , 56 , 57 ], although the shift towards early introduction of these foods has led to a corresponding reduction in age at diagnosis of these allergies. In addition to presenting later, nut and seafood allergies also tend to persist into adulthood, which will be covered more in the following sections (Table 1 ).…”
Section: Infancy and Early Childhoodmentioning
confidence: 99%
“…25 The hypoallergenic mutant of Cra a 4 based on the structural characteristics is expected to be applied in the prevention and control of food allergies caused by oyster products. 26 The main purpose of this study was to systematically investigate the association of disulfide bonds, conformational epitopes, and the Ca 2+ -binding region with immunoreactivity of Cra a 4. To identify the structure−allergenicity relationship of Cra a 4, different chemical denaturants were used to destroy the structure of Cra a 4.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It had been reported that hypoallergenic mutants of pollen allergen (Parietaria judaica) had lower IgE-binding activity and allergenicity in mice by site-directed mutation . The hypoallergenic mutant of Cra a 4 based on the structural characteristics is expected to be applied in the prevention and control of food allergies caused by oyster products …”
Section: Introductionmentioning
confidence: 99%
“…Seafood, including fish and shellfish, is a rich source of nutrients and antioxidants, making it a key component of the Mediterranean diet [1,2]. Known for providing essential protein and omega-3 fatty acids, seafood offers numerous cardiovascular health benefits [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Known for providing essential protein and omega-3 fatty acids, seafood offers numerous cardiovascular health benefits [3][4][5]. As a result, its consumption has surged in recent years, paralleling an increase in allergic reactions to seafood [1,2]. While shellfish includes both crustaceans and mollusks, research has traditionally focused on crustaceans, leaving studies on mollusk allergies, particularly gastropod allergies, notably sparse.…”
Section: Introductionmentioning
confidence: 99%